ANALYSIS OF THE SEASONAL IMPACT ON ISOTOPIC BASELINES OF DISSOLVED INORGANIC CARBON (DIC) IN COASTAL WATERS SPERMONDE, SOUTH SULAWESI - Wa Ode Rustiah; Alfian Noor; . Maming; Muhammad Lukman (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2019)
Stable carbon isotopes have been commonly used as indicators for assessing environmental changes in aquatic ecosystems. They can be used to study the dynamics of organic matter as for understanding the overall functioning of the ecosystem, the connectivity of estuaries with terrestrial and marine coastal habitats. The objective of this study is determining the seasonal natural effects over isotopic (13C/12C) baselines in monitoring CO2 storage in dissolved inorganic materials in Spermonde waters on the west coast of South Sulawesi to some outermost island. The results show that the stable carbon isotopic of DIC (d13C-DIC) in the wet season varied between -5.36 ‰ and -7.74 ‰. These value are higher than on dry season (-4.34 ‰ to -6.82 ‰). Likewise, DIC concentration in the rainy season ranged between 9.5 mg C/L and 11.7 mg C/L, while in the dry season it varied from 8.5 mg C/L to 9.3 mg C/L. The d13C-DIC and DIC concentrations decreased towards offshore, up to some of the outer islands. Increasing in the d13C-DIC in Spermonde waters indicate that the DIC is most likely enriched by atmospheric CO2(g), which is outnumbered those of aquatic photosynthesis. This study shows that different levels and composition of d13C-DIC stretch along different rivers are attributable to the varying landscapes and quality of organic matters.